The effects of CEP-37440, an inhibitor of focal adhesion kinase, in vitro and in vivo on inflammatory breast cancer cells. Issue 1 (December 2016) - Salem, Israa; Alsalahi, Manal; Chervoneva, Inna; Aburto, Lucy; Addya, Sankar; Ott, Gregory; Ruggeri, Bruce; Cristofanilli, Massimo; Fernandez, Sandra
Abstract Background Inflammatory breast cancer (IBC) is an aggressive type of advanced breast cancer with a poor prognosis. We recently found that focal adhesion kinase 1 (FAK1) is upregulated and phosphorylated (active) in IBC. In this study, we investigated the effect of CEP-37440, a dual inhibitor of FAK1 and anaplastic lymphoma kinase (ALK), using human IBC cell lines and preclinical models of IBC. Methods Cell proliferation assays were performed in the presence of several concentrations of CEP-37440 using IBC and triple-negative breast cancer non-IBC cell lines. In vitro, we studied the expression of total FAK1, phospho-FAK1 (Tyr 397), total ALK and phospho-ALK (Tyr 1604). In vivo, we tested CEP-37440 using FC-IBC02, SUM149, and SUM190 IBC xenograft mouse models. Results CEP-37440 at low concentration decreased the proliferation of the IBC cell lines FC-IBC02, SUM190, and KPL4, while not affecting the proliferation of normal breast epithelial cells. At higher concentration, CEP-37440 was also able to inhibit the proliferation of the IBC cell line MDA-IBC03 and the triple-negative non-IBC cell lines MDA-MB-231 and MDA-MB-468; the IBC cell line SUM149 showed a slight response to the drug. CEP-37440 decreased the cell proliferation of FC-IBC02, SUM190, and KPL4 by blocking the autophosphorylation kinase activity of FAK1 (Tyr 397). None of the cells evaluated expressed ALK. In vivo, after 7 weeks of CEP-37440 treatment, the SUM190, FC-IBC02, and SUM149 breast tumor xenografts were smaller in mice treated with 55 mg/kg bid CEP-37440 compared to the controls; the tumor growth inhibition (TGI) was 79.7 %, 33 %, and 23 %, respectively. None of the FC-IBC02 breast xenografts mice treated with CEP-37440 developed brain metastasis while 20 % of the mice in the control group developed brain metastasis. Expression array analyses in FC-IBC02 cells showed that CEP-37440 affects the expression of genes related to apoptosis, interferon signaling, and cytokines. Conclusions CEP-37440 is effective against some IBC cells that express phospho-FAK1 (Tyr 397), and its antiproliferative activity is related to its ability to decrease phospho-FAK1. Our results suggest that combinational therapies could be more effective than using CEP-37440 as a single agent.